PENERAPAN STRATEGI CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SENI MUSIK SISWA - Endang Sriningsih (Jurnal Didaktika Pendidikan Dasar, 2019)
The preliminary research showed that the average of student learning outcomes in Music Subjects is still in the low category. The reflection process shows that the previous teaching and learning process was not connected with the student's real life. The strategy of teaching and learning that connect and near to the student activities is contextual teaching and learning (CTL). The aims of this research are to describe: (1) the teacher activities while implementing CTL; (2) the student activities in the implementation of CTL; and (3) the increasing of student learning outcomes in playing musical instrument recorder in accordance with the notation of music after CTL process. The research methodology is Classroom Action Research (CAR) which consists of three cycles (Kemmis & Mc. Taggart). The model of CAR consists of four steps that are planning, actuating, observing, and reflection. This research was conducted in SMPN 4 Mataram with the subject of students in class IX 4 that consists of 29 people in the Odd semester of Academic Year 2017/ 2018. The results of the research showed an improvement of teacher activities in the first cycle to the second cycle and the second cycle to the third cycle around 13.51% and 7.14%. The improvement of student activities in the first cycle to the second cycle and the second cycle to the third cycle around 10.71% and 9.67%. Moreover, the improvement of teacher and students' activities lead to the improvement of student learning outcome on knowledge aspect which increased on the first cycle to the second cycle and the second cycle to the third cycle around 16 points and 12 points, and on the skills, aspect increased on the first cycle to the second cycle and the second cycle to the third cycle around 13 points and 8 points.